New diagnostic markers for the degree of liver fibrosis in children with chronic viral hepatitis - I. I. Nezgoda; L. V. Moroz; S. Singh; O. O. Singh (Kazimierz Wielki University, 2017)
The article presents results of the study which includes 41 children with chronic viral hepatitis B (CHB) and acute lymphoblastic leukemia (ALL), aged 3 to 17 years and all were at dispensary observation in the Vinnytsia Regional Infectious Disease Hospital, Ukraine from January 2016 to February 2017. The aim of this study was to determine the plasma osteopontin level (OPN) in children, depending on sex, viral load, and degree of fibrosis. It was found that the level of this glycoprotein in children with chronic hepatitis B with ALL was significantly higher (275.66 ± 22.32 ng / ml) than in control group children (92.65 ± 7.31 ng / ml) (p <0, 05). The highest rates of OPN were found in younger children, with an increase in age, it decreases. In 68.24% of patients with CHB with ALL occurs with significant fibrotic changes in the liver: F1 fibrosis was found in 34.15% of patients, F2 in 31.7% of patients, F3 in 2.44% of patients. With the increase in the degree of fibrosis in the liver, the level of OPN increases. Its minimum value was found in children without fibrosis F0 (169.61 ± 21.19 ng / ml), with fibrosis F1 - this figure is (214.57 ± 14.49 ng / ml), with F2 - its level rises (432.39 ± 30.59 ng / ml), the maximum value of OPN was diagnosed in patients with fibrosis F3 (472.52 ng / ml). Direct correlation (r = 0.577, p <0.001) between the degree of fibrosis and the level of OPN was detected. Thus, osteopontin can be used as a new biomarker for the liver fibrosis.